Sun Exposure and Reduced Risk of Multiple Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The association between red hair color (RHC) melanocortin 1 receptor genotype, past environmental sun exposure, and risk of multiple sclerosis (MS) was investigated in a population-based case-control study in Tasmania, Australia, involving 136 cases with MS and 272 controls.